Antibacterial and antioxidant activities of ethanolic extracts of Hibiscus escobariae Fryxell, Loxopterygium huasango R. Spruce and Croton ferrugineus Kunth (Revista Científica Ciencias Naturales y Ambientales, 2019)
This study has done phytochemical screening, quantification of flavonoids and total phenols, evaluation of antibacterial activity against three Gram positive bacterias (Staphylococcus aureus, Bacillus subtilis, Listeria monocytogenes), three Gram negatives (Escherichia coli, Pseudomonas aeruginosa, Vibrio parahaemolyticus) and the evaluation antioxidant activity of ethanolic extracts of Hibiscus escobariae, Loxopterygium huasango and Croton ferrugineus. The sample analysis employed phytochemical screening by Dominguez’s method, quantification of flavonoids by the aluminum chloride colorimetric method, quantification of total phenols by the Folin-Ciocalteu method, antibacterial activity by disk diffusion assay and antioxidant activity by DPPH method. In the phytochemical screening, the flavonoids and tannins were higher proportion, while alkaloids, quinones, anthraquinones, steroids and saponins were present in lower proportion. The flavonoid content varied in a range of 100.95 ± 1.73 and 995.42 ± 3.16 mg CE / g extract, in H. escobariae and L. huasango and the total phenol content varied in a range of 10.17 ± 0.22 a 314.72 ± 1.91 mg GAE/ g extract in C. ferrugineus and L. huasango, which also obtained the best antibacterial activity against all the strains evaluated with MIC that varied of 2.5 - 5 mg/mL and also obtained the best antioxidant activity with a IC50 of 0.1 mg/mL and 0.7 mg/mL for Croton ferrugineus with a significant difference p
Keywords: Antibacterial; Antioxidant; Croton ferrugineus; Flavonoids; Hibiscus escobariae; Loxopterygium huasango; Phenols; Phytochemical screening